If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3 + 5n) = 33 + -5n (3 * -4 + 5n * -4) = 33 + -5n (-12 + -20n) = 33 + -5n Solving -12 + -20n = 33 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. -12 + -20n + 5n = 33 + -5n + 5n Combine like terms: -20n + 5n = -15n -12 + -15n = 33 + -5n + 5n Combine like terms: -5n + 5n = 0 -12 + -15n = 33 + 0 -12 + -15n = 33 Add '12' to each side of the equation. -12 + 12 + -15n = 33 + 12 Combine like terms: -12 + 12 = 0 0 + -15n = 33 + 12 -15n = 33 + 12 Combine like terms: 33 + 12 = 45 -15n = 45 Divide each side by '-15'. n = -3 Simplifying n = -3
| 6x-46=4x+75 | | 2x^2+17a+36= | | 6x-46+4x+75=180 | | 93=p+24 | | 7w-12w=-15 | | 14-5n=-36 | | S-3.6=2.5 | | 9x^4-90x^3+8x^2= | | 93=p+9 | | 8(-2)=40 | | 4x+11=8x+7 | | 4x+11=8x+7 | | 70=-7z | | 4-0.5p=-0.5p+4 | | (x+3)(x-1)=2 | | 3x+16=5x-6 | | 2[-4(4x+4)+5(4x-4)]= | | 7(r+6)=-3r-38 | | 8x=9-5y(4) | | x+(x+45)=111 | | r+76=100 | | 25a+30= | | u-62=22 | | 5n-16-8n=66 | | -2(4-c)=.666666c | | 3q+5=3(q+1)+2 | | 7(x-8)=49 | | f(x)=kx^2+3x+2 | | -8x+1=7-7x | | -1s+5x= | | 17+5y=87 | | 2-4(x+1)=6 |